Farmers’ willingness to pay for weather and climate information services in sub-Saharan Africa: a systematic review with meta-analysis - Gouroubera, Mori W.; Segnon, Alcade C.; Tonle, Franck B. N.; Zougmoré, Robert B. (Frontiers in Climate, 2025)
Access to Weather and Climate Information Services (WCIS) is critical for strengthening farmers’ resilience to climate risks. Yet, understanding farmers’ willingness to pay (WTP) for WCIS and its determinants for designing sustainable delivery and financing mechanisms in sub-Saharan Africa (SSA) remains limited. This study synthesizes existing evidence on farmers’ WTP for WCIS in SSA through a systematic review with meta-analysis of 14 relevant publications involving 20 empirical studies covering 5,709 farmers across 11 countries. The pooled estimate indicates that approximately 75% (95% CI: 65–83%) of farmers are WTP for WCIS, with a higher preference for bundled services (86% [95% CI: 79–91%]) compared to standalone WCIS products (48% [95% CI: 35–62%]). On average, farmers are willing to pay 8.11 USD/year (95% CI: 3.20–13.02) for WCIS, with a higher amount (13.7 USD/year, 95% CI: 8.37–19.06) for bundled services compared to standalone WCIS (1.38 USD/year, 95% CI: 0.16–2.59). Key drivers of WTP include economic and financial factors (access to credit and farm size), ownership of Information and Communications Technology (ICT) devices (mobile phone and television), access to extension services and market information, perceived forecast accuracy, and awareness and exposure to climatic risks. In contrast, traditional socio-demographic variables such as age, gender, and education showed limited explanatory power. These findings underscore that while farmers value WCIS, the amount they are willing to pay to access WCIS remains very low, limiting the viability and sustainability of business models with revenue generation relying solely on farmers. The paucity of studies and the heterogeneity in the findings call for further research on farmers’ WTP for WCIS across geographical and socioeconomic contexts of the continent, with a focus on developing sustainable business models that engage the private sector to support effective climate information dissemination and build climate-resilient farming systems.